2021
DOI: 10.14814/phy2.14731
|View full text |Cite
|
Sign up to set email alerts
|

Profiling plasma‐extracellular vesicle proteins and microRNAs in diabetes onset in middle‐aged male participants in the ELSA‐Brasil study

Abstract: We measured plasma‐derived extracellular vesicle (EV) proteins and their microRNA (miRNA) cargos in normoglycemic (NG), glucose intolerant (GI), and newly diagnosed diabetes mellitus (DM) in middle‐aged male participants of the Brazilian Longitudinal Study of Adult Health (ELSA‐Brazil). Mass spectrometry revealed decreased IGHG‐1 and increased ITIH2 protein levels in the GI group compared with that in the NG group and higher serotransferrin in EVs in the DM group than in those in the NG and GI groups. The GI g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 81 publications
(101 reference statements)
0
24
0
Order By: Relevance
“…GPLD1 serves as a biomarker that effectively differentiates latent autoimmune diabetes in adults from type 2 diabetes in the early stage [46], and it was shown that the circulating GPLD1 concentration in diabetic rats could be restored to normal levels by exercise training [47]. Masi et al [48] found that TF may have predictive value for the occurrence of long-term complications in patients with diabetes, but the specific mechanisms remain to be studied. It has also been reported that RBP4 secreted by the liver and adipose tissue may be involved in insulin resistance, diabetes, and coronary artery disease [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…GPLD1 serves as a biomarker that effectively differentiates latent autoimmune diabetes in adults from type 2 diabetes in the early stage [46], and it was shown that the circulating GPLD1 concentration in diabetic rats could be restored to normal levels by exercise training [47]. Masi et al [48] found that TF may have predictive value for the occurrence of long-term complications in patients with diabetes, but the specific mechanisms remain to be studied. It has also been reported that RBP4 secreted by the liver and adipose tissue may be involved in insulin resistance, diabetes, and coronary artery disease [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, among analyzed miRs, miR-370-3p and miR-374b-5p expression changed during ADG in CHG. MiR-370-3p is suggested to be an important predictor of metabolic syndrome presence [ 17 ]. The dysregulation of miR-374b-5p has been implicated in several disorders, including obesity, calcific aortic stenosis, and ischemic stroke [ 54 ]. Their expression ties well with observed protein-mRNA changes of their target genes ( IRS1 , PI3K , PTEN ) in our research.…”
Section: Discussionmentioning
confidence: 99%
“…Among miRNAs, miRNA-370-3p is suggested to be an important predictor of visceral adiposity in MetS ( Ramzan et al, 2020 ). The dysregulation of miRNA-374b-5p has been implicated in several disorders, including obesity, ischemic stroke, etc ( Masi et al, 2021 ). Upregulation of miRNA-181a-5p and miRNA-23a-3p expression in adipocytes stimulates Akt activation ( Lozano-Bartolomé et al, 2017 ).…”
Section: Relationship Between the Akt Pathway And Visceral Adipositymentioning
confidence: 99%
“…The level of miRNA-135a ( Agarwal et al, 2013 ), miRNA-214, miRNA-202 ( Honardoost et al, 2018 ), miRNA-29a, miRNA-29b, miRNA-29c, miRNA-143, and miRNA-200 ( He et al, 2007 ; Jordan et al, 2011 ; Dou et al, 2013 ) can affect the activity of Akt and provide key targets to improving abnormal glucose metabolism and IR. The level of miRNA-370-3p ( Ramzan et al, 2020 ), miRNA-374b-5p ( Masi et al, 2021 ), miRNA-23a-3p ( Lozano-Bartolomé et al, 2017 ), miR-221 ( Huang et al, 2021 ), and miRNA-26b ( Xu et al, 2015 ) can affect Akt activity and improve MetS through key targets of lipid metabolism.…”
Section: Akt-related Genetic Factors For Metabolic Syndromementioning
confidence: 99%